ANALYSIS OF PROCUREMENT OF OFFICE FACILITIES AND INFRASTRUCTURE AT THE JAKARTA CIKINI LIBRARY - Sahli Nurdin; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
Facilities and infrastructure are the main support for productivity within a company. If a company wants a significant increase in productivity, the first thing to pay attention to is the facilities and tools available to employees. Office facilities and infrastructure such as office equipment and work space require special attention in procurement. If the procurement of office infrastructure is not carried out properly, it will result in disruption of work activities. The aim of this research is to determine the provision of infrastructure at Cikini Jakarta libraries. This research method uses a case study method, which is an in-depth research approach to certain cases or phenomena in a real context. The results of the research through observation and interviews show that the procurement of office infrastructure such as procurement of official vehicles, cleaning equipment, then schedules and obstacles in the procurement of infrastructure such as procurement schedules for example for vehicles or air conditioners are usually scheduled every three months and will be carried out for maintenance. Obstacles that occur when there is damage to infrastructure means we cannot immediately procure the goods, but must report it to the building manager. The researcher felt this obstacle himself when he was going to conduct the interview, there were several lifts and escalators that were not working. Even though various kinds of existing facilities and infrastructure are procured routinely and periodically, not all office facilities and infrastructure receive sufficient attention for procurement. This can be seen from the storage room for office equipment and machines which are not properly maintained and are not immediately repaired when damage occurs.